Response to John Goldingay’s The Theology of the Book of Isaiah - Grey, Jacqueline N. (Journal of pentecostal theology, 2016)
This review and the three that follow were originally presented as a panel discussion of John Goldingay’s The Theology of the Book of Isaiah presented at the Society for Pentecostal Studies Biblical Studies section at the 2015 Society for Biblical Literature meeting. This review first presents an overview of the structure of Goldingay’s monograph before exploring and critiquing its content. There are three main issues highlighted in this analysis of Goldingay’s book: 1. the question of the starting point for the development of a biblical theology of Isaiah; 2. the need for ethical reflection and application of the theologies of Isaiah that are developed in Goldingay’s book; and 3. how the theology of revelation explored in Goldingay’s book may contribute to a Pentecostal understanding of prophecy.